Digitalization of Education in the Medical University: Transformation Factors - Batyuk, Liliya; Zhernovnykova, Oksana (Educological discourse, 2023)
The COVID-19 pandemic provoked a sudden transition to distance learning and intensive development of the digital environment of universities in Ukraine, which, in fact, continues to this day. Considering the wide and sustainable implementation of digital technologies in the national health care system, there is a need to investigate the digitalization of education in institutions of higher medical education, and to assess how successful the process of forming the innovative infrastructure of a modern university and the range of possible consequences of the rapid implementation of digital education. The article examines the experience of organizing distance learning, which is regulated by regulatory documents, the conditions for the formation of electronic and digital infrastructure components in a modern university; study of the spectrum of possible consequences of the use of digital education in institutions of higher medical education. The concepts of «digital education» and «digital competence», «digital medical technologies» were analyzed. The educational process is considered, namely online courses and distance educational technologies, educational resources, virtual digital library. The implementation of educational disciplines in medicine using virtual simulators and augmented reality is analyzed. Considered the issues of organizational and management sphere in the medical university. Some applications were analyzed, namely, a digital campus, an electronic student card, a digital diploma, a digital footprint of a higher education applicant, a teacher's digital portfolio, etc. The image positioning of the medical university is considered, namely, the website of university, digital transformation of career guidance and employment processes; creation of a competence center at the university as a basis for improving the qualifications of professors and teaching staff based on the concept of continuous education. The positive and negative social effects of the use of digital technologies in the educational environment are analyzed.